Opioids and Traffic Safety – Focus on Buprenorphine - Soyka, M. (Pharmacopsychiatry, 2014)
Opioid maintenance therapy is a well-established first-line treatment approach in opioid dependence. The effects of opioids such as buprenorphine on cognitive functioning and driving ability are a matter of debate.A comprehensive review of studies of the effects of buprenorphine on traffic safety is presented.A number of recent epidemiological and road surveys indicate that opioids have a moderate risk for causing accidents compared to other drugs of abuse, such as alcohol. A number of neuropsychological studies, a few of which were prospective and used a randomized control group, have used standardized test batteries to measure domains relevant for psychomotor functioning and driving ability. Single doses of buprenorphine have been shown to induce some impairment in healthy volunteers, but less than found in chronic users. Some non-randomized studies indicate somewhat better cognitive performance of patients on buprenorphine than of those on methadone but this finding has not been demonstrated in randomized controlled trials.Opioids as a class of drugs induce some impairment of driving ability, but less than other psychotropic agents or drugs of abuse. Personality features such as impulsivity, sensation seeking, low risk perception and antisocial behaviour, comorbid psychiatric and neurological disorders and additional substance use of opioid users are of relevance for traffic safety. Buprenorphine does not cause more cognitive impairment than methadone or may even cause less. Caution is required when initiating treatment with buprenorphine. The risk for driving ability impairment is probably less under steady state conditions. Finally, higher doses of buprenorphine are probably not associated with more impairment.
Keywords: opioids; opioid dependence; buprenorphine; cognition; driving ability